2008
DOI: 10.3329/bjp.v4i1.1051
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine insecticides (DDT and heptachlor) in dry fish: traditional washing and cooking effect on dietary intake

Abstract: The concentrations of organochlorine insecticides (DDT and heptachlor) were investigated to estimate the effect of various washing and boiling/cooking to elucidate the concentration level we intake actually. For this study five most popular dry fish samples namely bombay duck (loittya), ribbon fish (chhuri), shrimp (chingri), chinese pomfret (rupchanda) and Indian salmon (lakhua) were analyzed. The highest concentrations of DDT and heptachlor were found 737.2 ppb (Indian salmon, normal) and 44.8 ppb (shrimp, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Washing fish prior to cooking also decreases heptachlor and total DDT contents in Bombay duck, ribbon fish, shrimp, Chinese pomfret, and Indian salmon. Washing with cold water reduced the contents of heptachlor and DDT by 19.0% to 47.7% and 14.8% to 39.2%, respectively; washing with hot water resulted in higher percentages of reduction for both pesticides, reducing heptachlor and DDT by 24.3% to 63.1% and 46.3% to 80.7%, respectively (Bhuiyan and others ). The higher percentages of reduction, resulting from hot water washing, in comparison with those resulting from cold water washing, may be due to the higher solubility of lipophilic compounds in hot water and their consequent removal from the fish.…”
Section: Impact Of Cooking On Agrochemical Contaminants Present In Mementioning
confidence: 99%
“…Washing fish prior to cooking also decreases heptachlor and total DDT contents in Bombay duck, ribbon fish, shrimp, Chinese pomfret, and Indian salmon. Washing with cold water reduced the contents of heptachlor and DDT by 19.0% to 47.7% and 14.8% to 39.2%, respectively; washing with hot water resulted in higher percentages of reduction for both pesticides, reducing heptachlor and DDT by 24.3% to 63.1% and 46.3% to 80.7%, respectively (Bhuiyan and others ). The higher percentages of reduction, resulting from hot water washing, in comparison with those resulting from cold water washing, may be due to the higher solubility of lipophilic compounds in hot water and their consequent removal from the fish.…”
Section: Impact Of Cooking On Agrochemical Contaminants Present In Mementioning
confidence: 99%
“…Among the adulterants/contaminants that are listed in Table 1, the main carcinogenic or cancer causing agents are formalin, coal tar, DDT, calcium carbide, sodium cyclamate, urea, cadmium, chromium, and arsenic. All of these contaminants or adulterants have been detected or reported to be present in different types of food in recent studies (Bhuiyan et al, 2009a;Uddin et al, 2011;Al-Rmalli et al, 2012;Naser et al, 2012;Mahfuz and Mahin, 2014;Nasreen and Ahmed, 2014). Occurrence of diarrhea has increased from 11 to 14% from 2011 to 2014 which could be attributed to increased water pollution and increased presence of diarrhea causing adulterants in foods such as ethylene oxide, saw dust, toxic colors shown in Table 1 (Khan, 2004;Health Bulletin, 2013Farooque, 2014).…”
Section: Public Health Perspective: Toxicity Continuummentioning
confidence: 97%
“…Though it shows clearly that ingestion through water is contributing higher compared to food intake, nevertheless intake via food has significant contribution. It is important to mention that it was assumed that 10% of the total food ingested are contaminated or adulterated whereas it has been reported that 50% of the total food ingested could be contaminated and adulterated (Khan, 2004;Bhuiyan et al, 2009a;Uddin et al, 2011;Naser et al, 2012;Ali, 2013a;Nasreen and Ahmed, 2014). Additionally, this analysis approximated that water with the contaminants found in the river/water sources are minimally treated and normally drank by the common people.…”
Section: Risk Assessment Of Contaminants and Adulterantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boling process is very effective in reducing DDT and heptachlor concentrations in dried fish (Bombay duck-loittya, ribbon fish-chhuri, shrimp-chingri, Chinese pomfret-rupchanda and Indian salmon-lakhua) [93]. It has been reported that frying process is effective in reducing α-HCH, β-HCH, γ-HCH, heptachlor, aldrin, heptachlor epoxide isomer B, pp′-DDE, endrin and pp'-DDT residues in commonly consumed fish (Clupea harengus L., Salmo salar L., Cyprinus carpio L., Salmotrutta m. fario L., Platichthys flesus L. and Gadus morhua L.) in Poland, and the most pronounced reduction is observed in β-HCH residues [94].…”
Section: The Effect Of Various Cooking and Freezing Processes On Contmentioning
confidence: 99%